2023
DOI: 10.3390/life13010204
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals Mediated Redox Signaling in Plant Stress Tolerance

Abstract: Abiotic and biotic stresses negatively affect plant cellular and biological processes, limiting their growth and productivity. Plants respond to these environmental cues and biotrophic attackers by activating intricate metabolic-molecular signaling networks precisely and coordinately. One of the initial signaling networks activated is involved in the generation of reactive oxygen species (ROS), reactive nitrogen species (RNS), and reactive sulfur species (RSS). Recent research has exemplified that ROS below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 166 publications
0
0
0
Order By: Relevance
“…However, the presence of too many ROS can alter the overall redox balance and lead to oxidative damage to biological macromolecules, such as nucleic acids, proteins, and lipids. 39 The accumulation of MDAone of the most significant byproducts of membrane lipid peroxidationcan exacerbate membrane damage. 40 The results of this study demonstrated that SA treatment considerably raised MDA content (P < 0.05), as well as H 2 O 2 and O 2 − fluorescence intensity, in comparison to the control (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of too many ROS can alter the overall redox balance and lead to oxidative damage to biological macromolecules, such as nucleic acids, proteins, and lipids. 39 The accumulation of MDAone of the most significant byproducts of membrane lipid peroxidationcan exacerbate membrane damage. 40 The results of this study demonstrated that SA treatment considerably raised MDA content (P < 0.05), as well as H 2 O 2 and O 2 − fluorescence intensity, in comparison to the control (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction, gene expression control, immunological response, and the mediation of numerous physiological processes in cells and organisms are all regulated by ROS. However, the presence of too many ROS can alter the overall redox balance and lead to oxidative damage to biological macromolecules, such as nucleic acids, proteins, and lipids 39 . The accumulation of MDA – one of the most significant byproducts of membrane lipid peroxidation – can exacerbate membrane damage 40 .…”
Section: Discussionmentioning
confidence: 99%